2013
DOI: 10.1155/2013/307145
|View full text |Cite
|
Sign up to set email alerts
|

miR156- and miR171-Binding Sites in the Protein-Coding Sequences of Several Plant Genes

Abstract: We identified the interaction sites of several miRNAs with the mRNAs from paralogs and orthologs of the SPL and HAM genes in A. thaliana. miRNAs from the miR156 and miR157 families in A. thaliana are shown to have binding sites within the mRNAs of SPL genes. The ath-miR156a–j binding sites located in the mRNAs of the SPL paralogs contain the sequence GUGCUCUCUCUCUUCUGUCA. This sequence encodes the ALSLLS motif. miR157a–d bind to mRNAs of the SPL family at the same site. We suggest merging the miR156 and miR157… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
(29 reference statements)
2
18
0
Order By: Relevance
“…For all miR2102-5p, miR2919, and miR5075-3p binding sites, nucleotide conservation is present compared to the flanking nucleotides of mRNA target genes. With the complete complementarity of the nucleotides miRNA and mRNA (ΔG/ΔGm = 100%) of the target genes, absolute conservatism of the site along the entire binding site should be observed, as previously shown (Atambayeva et al, 2017; Bari, Orazova & Ivashchenko, 2013; Bari et al, 2014; Yurikova et al, 2019). When the ΔG/ΔGm value changes from 94% to 100% (Table 1), the basis for the interaction of the nucleotides miR2102-5p, miR2919 and miR5075-3p and mRNA are G-С pairs.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…For all miR2102-5p, miR2919, and miR5075-3p binding sites, nucleotide conservation is present compared to the flanking nucleotides of mRNA target genes. With the complete complementarity of the nucleotides miRNA and mRNA (ΔG/ΔGm = 100%) of the target genes, absolute conservatism of the site along the entire binding site should be observed, as previously shown (Atambayeva et al, 2017; Bari, Orazova & Ivashchenko, 2013; Bari et al, 2014; Yurikova et al, 2019). When the ΔG/ΔGm value changes from 94% to 100% (Table 1), the basis for the interaction of the nucleotides miR2102-5p, miR2919 and miR5075-3p and mRNA are G-С pairs.…”
Section: Resultssupporting
confidence: 58%
“…2). The conservatism of such bonds between miRNAs and their target genes was established by us for many associations of miRNAs and their target genes in animals and plants (Atambayeva et al, 2017; Bari, Orazova & Ivashchenko, 2013; Bari et al, 2014; Yurikova et al, 2019). These bonds have persisted over tens of millions of years of evolution and indicate the early emergence of the process of regulation by miRNA molecules of target gene expression in animals and plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the miRNA171 and 170 target several GRAS proteins (Llave et al, 2002;Bari et al, 2013). It has been shown that the miRNA171 and 170 target several GRAS proteins (Llave et al, 2002;Bari et al, 2013).…”
Section: Regulation Of Gras Gene Expression By Mirnamentioning
confidence: 99%